System architecture, challenges and prospects of 2S-city construction - Chunye MA; Hao CHEN; Jiankun PENG; Shuangzhi YU (Dianxin kexue)
As the most important application scenario in the process of the transformation of China’s automobile industry to electrification, intelligence, connectivity and sharing, the pilot project of smart city infrastructure and intelligent connected vehicles (2S-city) is still in the transition and demonstration stage, and there is still a distance from commercialization and marketization.Starting from the core problems and strategic significance of 2S-city construction, the roadside infrastructure architecture and platform function construction were described, the positive development process of system engineering that should be followed was introduced, and the future development orientation and suggestions were analyzed.